(untitled) (Research, Society and Development, 2021)
Introduction: The pirarucu is a species native to the Amazon, belonging to the order Osteoglossiformes, Arapaimidae. It is a fish with high economic importance and a very growing commercial interest, due to its favorable characteristics for cultivation, such as: high growth rate (up to 10 kg in the first year), high rusticity in handling, adaptability to artificial feeding and high utilization of the carcass (51-57%). Objective: The study starts from a bibliographical survey about articles about alterations in the postharvest microbiological quality of pirarucu. Methodology: This is a descriptive bibliographic review. Results and Discussions: Frequent use of Good Handling Practices, HACCP (Hazard Analysis and Critical Control Points) is essential so that there are always quality and safe fish. Studies prove that the combination of texture, appearance and flavor in food is strongly essential for consumer acceptance, for the control of food quality, knowledge of the composition of food in Brazil is essential. It is necessary to handle the meat of the fish carefully in the production process so as not to run the risk of contamination. Conclusion: Pirarucu is a fish of high cultural and commercial value. Knowledge of the factors involved (physical-chemical, microbiological, sensory) in the progression of deterioration is essential for food security for end consumers and for processing and ideal storage protocols in industries.